2019
DOI: 10.3390/nu11071599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Dose–Response Relationship between Meal Protein Content and Postprandial Thermogenesis: Effect of Sex and the Oral Contraceptive Pill

Abstract: Implementation of efficacious dietary interventions to regulate energy balance requires understanding of the determinants of individual response. To date, information regarding individual variability in response to elevated meal protein content is lacking. This study investigates whether sex and/or oral contraceptive pill (OCP) use play a role in the response to elevated meal protein in 21 healthy young adults (seven men, seven women not taking OCP, and seven women who were OCP users). Participants consumed ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 24 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Disagreements were resolved by bilateral consensus. With the exception of the study by Eck et al 146 in which the methodological quality was rated as strong, corresponding to a low risk of bias, the methodological quality of all other studies [147][148][149][150][151][152][153][154] was only rated as moderate (Tables 3 and 4).…”
Section: Data Analysis and Risk Of Bias Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Disagreements were resolved by bilateral consensus. With the exception of the study by Eck et al 146 in which the methodological quality was rated as strong, corresponding to a low risk of bias, the methodological quality of all other studies [147][148][149][150][151][152][153][154] was only rated as moderate (Tables 3 and 4).…”
Section: Data Analysis and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Our systematic review identified a total of 10 studies investigating the effects of medication with natural and synthetic estrogens on REE and encompassing 461 healthy normal-weight and overweight women (Tables 1 and 2). [146][147][148][149][150][151][152][153][154][155] The 10 included studies consisted of six studies in which estrogens were used in the context of HC 146,[149][150][151][152]154 and four studies in which estrogens were used in the context of MHT. 147,148,153,155 Study designs were either RCTs, 150,151,153 prospective cohort studies, 147 or cross-sectional studies.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
See 3 more Smart Citations